Determinants of Risk Prevention for Money Laundering and Terrorist Financing (ML/TF) in Real Sector (2019)
This study is placed in the field of knowledge of the risk management. The purpose is to identify determinants of risk prevention for money laundering and terrorist financing ML/TF in the real sector. In the study we set out three variables: administration, environmental conditions and strategic allies. The research is qualitative, descriptive and is based on case study with the implementation of risk management system ML/TF, SARLAFT, in a large company in the real sector in Colombia. Risk prevention of ML/TF protects organizations against legal and reputational risk, while leading to the appropriation of administrative and management tools aligned with environmental conditions and its strategic allies, decisive and correlated factors that define safely. The shield against the risk of ML/TF decreases the rank of uncertainty in the development of business activities as it induces a transparent, safe and permanent control associated with each of the subjects involved, which ultimately give guarantee of sustainability.